Forestry : an international journal of forest research. - Institute of Chartered Foresters (Great Britain) (Oxford : Oxford University Press, 1927)
The aim of the journal is to publish high quality articles and reviews on all aspects of research, practice and policy that inform and promote the sustainable management of forests and trees. The journal is inclusive of all subjects, geographical zones and study locations, including trees in urban environments, plantations and natural forests.
"Published on behalf of The Institute of Chartered Foresters"--Home page.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Forests and forestry -- Periodicals; Forests and forestry -- Research -- Periodicals